1996
DOI: 10.1029/95jd02143
|View full text |Cite
|
Sign up to set email alerts
|

Validation of nitric oxide and nitrogen dioxide measurements made by the Halogen Occultation Experiment for UARS platform

Abstract: The Halogen Occultation Experiment (HALOE) experiment on Upper Atmosphere Research Satellite (UARS) performs solar occultation (sunrise and sunset) measurements to infer the composition and structure of the stratosphere and mesosphere. Two of the HALOE channels, centered at 5.26 gm and 6.25 gm, are designed to infer concentrations of nitric oxide and nitrogen dioxide respectively. The NO measurements extend from the lower stratosphere up to 130 km, while the NO2 results typically range from the lower stratosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 32 publications
3
94
0
Order By: Relevance
“…This harmonic climatology has been derived from satellite measurements by UARS/HALOE (Gordley et al, 1996) and SPOT-4/POAM-III (Randall et al, 1998) and complementary information from ground-based measurements from the Network for the Detection of Atmospheric Composition Change (NDACC). The stratospheric NO 2 profiles are time dependent and given for 16 latitude bands.…”
Section: Air Mass Factor and Initial Total Vcd Computationsmentioning
confidence: 99%
“…This harmonic climatology has been derived from satellite measurements by UARS/HALOE (Gordley et al, 1996) and SPOT-4/POAM-III (Randall et al, 1998) and complementary information from ground-based measurements from the Network for the Detection of Atmospheric Composition Change (NDACC). The stratospheric NO 2 profiles are time dependent and given for 16 latitude bands.…”
Section: Air Mass Factor and Initial Total Vcd Computationsmentioning
confidence: 99%
“…This study uses HALOE version 19 NO and NO 2 , which have very small differences relative to v17 (James M. Russell III, Hampton University, personal communication, December 2015). Gordley et al (1996) found that above 25 km HALOE v17 NO tended to agree with correlative satellite and balloon-based measurements within 15 %, but with a maximum low bias reaching 35 %. Also, above 25 km HALOE v17 NO 2 agreed with correlative satellite, balloon, and ground-based measurements to within 15 %.…”
Section: Solar Occultation Instruments 231 Haloe On the Upper Atmosmentioning
confidence: 90%
“…The NO retrievals have a vertical resolution of 4 km at altitudes below ∼ 60 km (degrading to 7 km at higher altitudes), and the NO 2 retrievals have a vertical resolution of 2 km. The HALOE version 17 NO and NO 2 data were validated by Gordley et al (1996). This study uses HALOE version 19 NO and NO 2 , which have very small differences relative to v17 (James M. Russell III, Hampton University, personal communication, December 2015).…”
Section: Solar Occultation Instruments 231 Haloe On the Upper Atmosmentioning
confidence: 99%
“…Therefore, this feature would be more likely due to a limitation of the HALOE and POAM III instruments for measuring NO 2 at these low altitude levels. The possible error sources on the HALOE and POAM III data are described in detail in Gordley et al (1996) and Randall et al (2002). A source of systematic error is the strong variations of NO 2 along a solar occultation measurement line of sight.…”
Section: Haloe Comparisonsmentioning
confidence: 99%
“…HALOE was launched on board the Upper Atmosphere Research Satellite (UARS) in September 1991 (Gordley et al, 1996). As for POAM III, the satellite instrument probes the atmosphere in solar occultation.…”
Section: Haloe Comparisonsmentioning
confidence: 99%